2020
DOI: 10.3390/w12092507
|View full text |Cite
|
Sign up to set email alerts
|

Improved Short-Term Microbial Degradation in Circulating Water Reducing High Stagnant Atrazine Concentrations in Subsurface Sediments

Abstract: The triazine herbicide atrazine easily leaches with water through soil layers into groundwater, where it is persistent. Its behavior during short-term transport is poorly understood, and there is no in situ remediation method for it. The aim of this study was to investigate whether water circulation, or circulation combined with bioaugmentation (Pseudomonas sp. ADP, or four isolates from atrazine-contaminated sediments) alone or with biostimulation (Na-citrate), could enhance atrazine dissipation in subsurface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Enzymes such as hydrolases and peroxidases or cytochrome P450 enzymatic complex present in various fungus and bacteria ( Pleurotus ostreatus , Pseudomonas species , Acinetobacter , Burkholderia , Methylobacterium , Rhodococcus , Sphingomonas , Streptomyces , Variovorax , or Williamsia ) showed a rather high potential in the degradation process of the atrazine group as well. These are also naturally biodegraded by microbial communities such as Paenarthrobacter aurescens and their genome scale metabolic models. , Mechanistic studies on the cometabolic biodegradation of atrazine indicated that cytochrome P450 monooxygenases catalyze degradation of this herbicide through several hydroxy-, dechlorinated, or dealkylated metabolites. The obtained metabolomics data revealed that atrazine induced oxidative stress and disruption of the carbon and nitrogen metabolism cause an increase in the membrane fluidity and induce lipid peroxidation as well …”
Section: From Fundamentals To Practical Improvements In Catalytic Pro...mentioning
confidence: 99%
“…Enzymes such as hydrolases and peroxidases or cytochrome P450 enzymatic complex present in various fungus and bacteria ( Pleurotus ostreatus , Pseudomonas species , Acinetobacter , Burkholderia , Methylobacterium , Rhodococcus , Sphingomonas , Streptomyces , Variovorax , or Williamsia ) showed a rather high potential in the degradation process of the atrazine group as well. These are also naturally biodegraded by microbial communities such as Paenarthrobacter aurescens and their genome scale metabolic models. , Mechanistic studies on the cometabolic biodegradation of atrazine indicated that cytochrome P450 monooxygenases catalyze degradation of this herbicide through several hydroxy-, dechlorinated, or dealkylated metabolites. The obtained metabolomics data revealed that atrazine induced oxidative stress and disruption of the carbon and nitrogen metabolism cause an increase in the membrane fluidity and induce lipid peroxidation as well …”
Section: From Fundamentals To Practical Improvements In Catalytic Pro...mentioning
confidence: 99%
“…Although groundwater sediment slurries were known to contain at least atrazine-degrading microorganisms, no microbial degradation was observed, as the complex formation ability of atrazine with sediment colloids may have inhibited bioavailability . Microbial numbers in the sediments have varied between 3.2-3.7 × 10 7 cells g −1 based on phospholipid fatty acids (PLFAs), while cultured microbial numbers in the sediment slurries without additives have varied between 0.1-6.7 × 10 4 cfu mL −1 (Mattsson et al, 2015;Liu et al, 2020). The average copy numbers of bacterial, archaeal, and fungal genes in boreal arable soils have been 0.86-1.3 × 10 10 , 1.9-3.7 × 10 7 , and 2.7-7.9 × 10 8 copies g −1 dry soil, while total-C and total-N concentrations have varied between 3.95-5.11 and 0.15-0.20 mg g −1 (Peltoniemi et al, 2021).…”
Section: Compost-peat-sand Mixture and Pesticide Dissipation In Soil And Sediment Slurriesmentioning
confidence: 99%